ALBANIAN – GREEK DICTIONARIES, COMPILED IN THE 90’S - Ksera, Kostando (European Scientific Journal, ESJ, 2014)
The compiling of Greek - Albanian and Albanian - Greek dictionaries after the 90’s has been a necessity due to the contacts which were established between the Greek and Albanian people after the fall of Communism in Albania and after the Albanian people came out of the half- century isolation. The efforts for compiling bilingual dictionaries during this period have been very important although there didn’t exist models which could be used to compile such dictionaries